Speculative Satire in Contemporary Literature and Film Rant Against the Regime (Taylor & Francis, 2021)
Since 1980, when neoliberal and neoconservative forces began their hostile takeover of western culture, a new type of political satire has emerged that works to unmask and deter those toxic doctrines. Literary and cultural critic Kirk Combe calls this new form of satire the Rant. The Rant is grim, highly imaginative, and complex in its blending of genres. It mixes facets of satire, science fiction, and monster tale to produce widely consumed spectacles-major studio movies, popular television/streaming series, bestselling novels-designed to disturb and to provoke. The Rant targets what Combe calls the Regime. Simply put, the Regime is the sum of the dangerous social, economic, and political orthodoxies spurred on by neoliberal and neoconservative polity. Such practices include free-market capitalism, corporatism, militarism, religiosity, imperialism, racism, patriarchy, and so on. In the Rant, then, we have a unique and wholly contemporary genre of political expression and protest: speculative satire.
English
Keywords: International relations; Literary studies: fiction, novelists and prose writers; Literature: history and criticism; Political ideologies and movements; Popular culture; Television; satire,political satire,science fiction,speculative fiction,dystopia,dystopian fiction,neoliberalism,neoconservatism,genre studies,cultural studies,capitalism,individualism,surveillance,marxism,socialism,Neoliberal corporatism,Speculative satire,Literature and film,Science fiction,Terry Gilliam's film,Speculative Satire,MaddAddam Trilogy,Young Man,MaddAddam,Timeless,Handmaid's Tale,Cognitive Estrangement,Surveillance Capitalism,Monster Tale,Workplace Abuse,Blade Runner,Shoshana Zuboff,Black Mirror,Menippean Satire,Roundabout,Feminist Fabulation,Lives,Chronic,America,North American Free Trade Agreement,Modern Satire,White Monster,International Monetary Fund,Horror Movie,God's Gardeners